Habitação "popular" de mercado : relações com o ambiente urbano na região metropolitana de Aracaju (SE) - Nascimento, Manuela Maria Pereira do (2014)
Currently, the actions of housing provision in Brazil have a high degree of institutional and financial complexity, in despite of their massive divulgation in overly simple propagandas. It is observed that the implementation of the housing policies is motivated by interests related to the accelerated growth of the housing production in national level. Therefore, in several cases, such policies are not in connection with the regional dynamics and the local environmental demands. In view of this, the present research is justified by the needed of an analysis of the deployments and effects of the new Brazilian housing policies, situating it in the context of the intrametropolitan differences. It was defined as general objective: analyze the housing expansion in the metropolitan zone of Aracaju (SE) - MZA between the years of 2000 and 2013, taking in to account it relations with the urban environment, infrastructure situation and the arising of new agglomerates of housing buildings. The bibliographical and documental research, the survey of secondary data, as well as the direct observation and the photographic survey done in field allowed to identify, from socioenvironmental indicators and cartographic analyzes, the areas of MZA with densification of housing built with resources of the government obtained through of financings started in the 2000 decade. It was analyzed the conditions of urban infrastructure of the new occupied spaces by categories of analysis established. Considering the frame observed from the evolution of the quantity, of the location and of the types of buildings that emerged in the MZA; from the typologies of the domiciles and the characteristics of the evolution and distribution of the population, it can be perceived that the intense provision in market popular housing will, until a certain point, be justified by the diminution of a housing deficit based in objective terms. It was evidenced that the effects of the housing policy implemented between the years of 1980 and 1990 and the housing shortages certainly should to move in the sense of the regularization of precarious settlements and improvement of the habitability conditions for the residential unities that were massively implanted until now. If these movements do not occur, the new condominiums built with the perspective of the supply to the needed of the middle class will consist in an big volume of buildings that will be rented by families that have conditions to migrate to newer housings and get out from areas with little urban infrastructure, or just that desire to live in these new spaces, but cannot to buy the new buildings and are influenced by the massive divulgation of the advantages of to live in the closed condominiums. In the evaluation of the interfaces between the housing provision and the natural constraints in the MZA, it can be stated that the new fronts of occupation are mostly in lands that already were semi-grounded or grounded since 2004, however located to the margin of areas of natural content that must be conserved. The frontier area between Aracaju and São Cristóvão (the neighborhoods of Jabotiana and Cabrita) corresponds to the portion of the MZA where it is found the bigger events of dismount of natural characteristics. Finally, with respect to the questions formulated for the research, it can be stated that the applications of the federal resources in housing does not occur in agreement with the socioenvironmental dimensions established in their policies and programs in the areas that are most affected.